Lutetium oxide (Lu2O3) gate dielectric fabricated by pulsed laser deposition - Peter Darmawan (2010)
The aim of this project is to investigate the suitability of rare-earth oxide as gate dielectric, in particular Lu2O3. There are three main chapters, in which the properties of Lu2O3 film, the effect of post-deposition treatments on Lu2O3 film as well as the properties of Lu2O3 on the next generation of semiconductor substrate are discussed in detail.